Classification of Bangla regional languages and recognition of artificial Bangla speech using deep learning - Hossain, Prommy Sultana (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2022.